Challenges on designing electrostatic discharge protection solutions for low power electronics - Liou, Juin J. (Proceedings of the 2013 International Symposium on Low Power Electronics and Design, 2013)
Electrostatic discharge (ESD) is a process in which a finite amount of charge is transferred from one object (i.e., human body) to the other (i.e., microchip). This process can result in a very high current passing through the object within a very short period of time [1-2]. When a microchip or electronic system is subject to an ESD event, the huge ESD-induced current can likely damage the microchip and cause malfunction to the electronic system if the heat generated in the object cannot be dissipated quickly enough. It is estimated that about 35% of all damaged microchips are ESD related, resulting in a revenue loss of several hundred million dollars in the global semiconductor industry every year [3]. The continuing diminishing in the size of MOS devices makes the ESD-induced failures even more prominent, and one can predict with certainty that the availability of effective and robust ESD protection solutions will become a critical component to the successful development of the CMOS-based integrated circuits [4-7].